TITAN'S SURFACE BRIGHTNESS TEMPERATURES - Jennings, D; Flasar, F; Kunde, V; Samuelson, R; Pearl, J; Nixon, C; Carlson, R; Mamoutkine, A; Brasunas, J; Guandique, E; Achterberg, R; Bjoraker, G; et al. (Institute of Physics Publishing, 2009)
Radiance from the surface of Titan can be detected from space through a spectral window of low opacity in the thermal infrared at 19 μm (530 cm -1). By combining Composite Infrared Spectrometer observations from Cassini's first four years, we have mapped the latitude distribution of zonally averaged surface brightness temperatures. The measurements are corrected for atmospheric opacity as derived from the dependence of radiance on the emission angle. At equatorial latitudes near the Huygens landing site, the surface brightness temperature is found to be 93.7 0.6 K, in excellent agreement with the in situ measurement. Temperature decreases toward the poles, reaching 90.5 0.8 K at 87°N and 91.7 0.7 K at 88°S. The meridional distribution of temperature has a maximum near 10°S, consistent with Titan's late northern winter. © 2009 The American Astronomical Society. All rights reserved.